Blood lactate as an indicator of match intensity in female wrestling - Hübner-Wozniak, E.; Kosmol, A. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The aim of the present study was to examine wrestling match intensity in women and to compare with men basing on the post match blood lactate concentration. Summary: This study is the first to conduct an evaluation of post match blood lactate concentration in female wrestlers. It is well known that blood lactate concentration after short-term, maximal exercise is higher in men then in women. However very high blood lactate concentration after matches both in male and female athletes demonstrating that the anaerobic metabolism was the dominant energy source during wrestling. The results of this study suggest that a specific anaerobic training programme should be similar for female and male free style wrestlers.